Epilepsy-associated genes. (January 2017) - Wang, Jie; Lin, Zhi-Jian; Liu, Liu; Xu, Hai-Qing; Shi, Yi-Wu; Yi, Yong-Hong; He, Na; Liao, Wei-Ping
Highlights: We summarized 977 epilepsy-associated genes, which were divided into 4 categories according to the manifestation of epilepsy in phenotypes. 84 epilepsy genes, i.e., genes that only cause epilepsies or syndromes with epilepsy as the core symptom. 73 neurodevelopment-associated genes, i.e., genes associated with gross brain developmental malformations and epilepsies. 536 epilepsy-related genes, i.e., genes associated with gross physical, or other systemic abnormalities and accompanied by epilepsy or seizures. 284 potential epilepsy-associated genes, i.e., genes that require further verification. Abstract: Development in genetic technology has led to the identification of an increasing number of genes associated with epilepsy. These discoveries will both provide the basis for including genetic tests in clinical practice and improve diagnosis and treatment of epilepsy. By searching through several databases (OMIM, HGMD, and EpilepsyGene) and recent publications on PubMed, we found 977 genes that are associated with epilepsy. We classified these genes into 4 categories according to the manifestation of epilepsy in phenotypes. We found 84 genes that are considered as epilepsy genes: genes that cause epilepsies or syndromes with epilepsy as the core symptom. 73 genes were listed as neurodevelopment-associated genes: genes associated with both brain-development malformations and epilepsy. Several genes (536) were epilepsy-related: genes associated with both physical or other systemic abnormalities and epilepsy or seizures. We found 284 additional genes putatively associated with epilepsy; this requires further verification. These integrated data will provide new insights useful for both including genetic tests in the clinical practice and evaluating the results of genetic tests. We also summarized the epilepsy-associated genes according to their function, with the goal to better characterize the association between genes and epilepsies and to further understand the mechanisms underlying epilepsy.